Mathematical Modelling On Transportation Method Apllication For Rice Distribution Cost Optimization - Azizah, Nuril Lutvi (CAUCHY, 2019)
RASKIN/RASTRA is a rice distribution program for the poor family with the aim of improving food security starting from the household scale. The Aim of this study is to determine whether the mathematics modelling can use in the transportation methods to provide an efficient solution of costs on the rice distribution in the region of Sidoarjo. The method used in this research is the NWC (Northwest Corner) method used to analyze the initial fiscal solution, and refined by MODI (Modified Distribution) to analyze the most optimal cost. From the calculation by transportation method, the optimum cost is lower than the company's calculation of Rp 85.186.040 while the cost of the company's calculation is Rp 87.209.690,750. Thus the use of transportation methods can save RASTRA's distribution cost of Rp 2.023.650,750.